2006
DOI: 10.1105/tpc.106.043695
|View full text |Cite
|
Sign up to set email alerts
|

Tung Tree DGAT1 and DGAT2 Have Nonredundant Functions in Triacylglycerol Biosynthesis and Are Localized to Different Subdomains of the Endoplasmic Reticulum

Abstract: Seeds of the tung tree (Vernicia fordii) produce large quantities of triacylglycerols (TAGs) containing ;80% eleostearic acid, an unusual conjugated fatty acid. We present a comparative analysis of the genetic, functional, and cellular properties of tung type 1 and type 2 diacylglycerol acyltransferases (DGAT1 and DGAT2), two unrelated enzymes that catalyze the committed step in TAG biosynthesis. We show that both enzymes are encoded by single genes and that DGAT1 is expressed at similar levels in various orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
584
4
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(629 citation statements)
references
References 80 publications
36
584
4
5
Order By: Relevance
“…Many studies have shown that Arabidopsis DGAT1 is important for TAG biosynthesis, whereas DGAT2 is not a major determining factor (Shockey et al, 2006). In addition, although PDAT1 and DGAT1 have overlapping functions for TAG synthesis in Arabidopsis , the transcription profile of PDAT1 changed less than that of DGAT1 when N concentration was reduced.…”
Section: Abi4 Is Essential For the Activation Of Dgat1 Expression Inmentioning
confidence: 99%
“…Many studies have shown that Arabidopsis DGAT1 is important for TAG biosynthesis, whereas DGAT2 is not a major determining factor (Shockey et al, 2006). In addition, although PDAT1 and DGAT1 have overlapping functions for TAG synthesis in Arabidopsis , the transcription profile of PDAT1 changed less than that of DGAT1 when N concentration was reduced.…”
Section: Abi4 Is Essential For the Activation Of Dgat1 Expression Inmentioning
confidence: 99%
“…This greater desaturation occurring on PC is likely an important reason for the increased 18:3n-3 content, suggesting that the enzymes taking over the TAG production from DGAT1 are allowed to access acyl groups at a later stage of desaturation, due to a relatively higher activity of FAD2/FAD3 or localization to different subdomains within the ER. A previous study has shown that DGAT1 and DGAT2 of tung tree localizes to different subdomains of the ER (Shockey et al, 2006), whereas it is currently not known if this is true also for PDAT. Our microsomal data, however, suggest that there is more to it than increased desaturation in the DGAT1-silencing lines.…”
Section: Dgat1 Down-regulationmentioning
confidence: 99%
“…DGAT1 is localized in the endoplasmic reticulum (ER), and the enzyme contributes significantly to oil accumulation in Arabidopsis seeds (Zhang et al, 2009). DGAT2 has been shown to be important in plants accumulating unusual fatty acids in their seeds, such as castor bean (Ricinus communis; Kroon et al, 2006) and tung tree (Vernicia fordii; Shockey et al, 2006). However, when DGAT2 is knocked out in Arabidopsis, neither the oil content nor the fatty acid profile is affected, and they show no difference compared with the mutant of DGAT1 when both genes are knocked out (Zhang et al, 2009).…”
Section: Dgat1 Down-regulationmentioning
confidence: 99%
“…Castor bean DGAT2 prefers ricinoleoyl-DAG acceptors (46), and its coexpression with the castor bean hydroxylase increases ricinoleic accumulation in Arabidopsis seeds (47). DGAT2 also has been studied in the Tung tree (which accumulates conjugated FAs in TAG), and it is localized to a subdomain of the ER that is different from that of DGAT1, suggesting that these two proteins may cooperate to synthesize TAG in Tung seeds but in spatially distinct subcellular locations (48). Although DGAT2 has been examined mostly in plant species with unusual FAs (47-50), it likely contributes to TAG accumulation in plants that do not accumulate unusual FAs based on expression levels in palm, olive, and other plants, even though its relative contribution may vary between species.…”
Section: Conventional Kennedy Pathwaymentioning
confidence: 99%